2015
DOI: 10.1097/j.pain.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for the development of persistent pain after breast cancer surgery

Abstract: Previous studies have reported that 15% to 25% of patients treated for breast cancer experience long-term moderate-to-severe pain in the area of surgery, potentially lasting for several years. Few prospective studies have included all potential risk factors for the development of persistent pain after breast cancer surgery (PPBCS). The aim of this prospective cohort study was to comprehensively identify factors predicting PPBCS. Patients scheduled for primary breast cancer surgery were recruited. Assessments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
177
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 39 publications
9
177
3
1
Order By: Relevance
“…The prevalence of pain at 21 months following surgery reported in our study is consistent with previous findings [2,8] as were the rates of moderate-to-severe persistent pain [8,10,27]. However, our findings differed to those of Andersen et al [11] who reported lower rates of moderate-to-severe pain in their cohort at rest and during movement at 1 year followup. The basis for these differences is not clear as inclusion criteria were similar for all studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The prevalence of pain at 21 months following surgery reported in our study is consistent with previous findings [2,8] as were the rates of moderate-to-severe persistent pain [8,10,27]. However, our findings differed to those of Andersen et al [11] who reported lower rates of moderate-to-severe pain in their cohort at rest and during movement at 1 year followup. The basis for these differences is not clear as inclusion criteria were similar for all studies.…”
Section: Discussionsupporting
confidence: 86%
“…Known independent risk factors for developing persistent pain following treatment for BC include younger age [3,[7][8][9][10][11], invasive surgical intervention [7,8,[11][12][13][14], high acute post-operative pain [8,13] and adjuvant radiation therapy following surgery [7,[12][13][14]; post-operative pain and neuropathic symptoms have also been implicated [11]. Recent studies have also identified higher body mass index [3,9,15], sleep disturbance, fatigue [12] as well as psychosocial factors [9,10,12] to be significantly associated with persistent pain.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pain which can begin after surgery may last for several years or even permanently. [3][4][5][6][7] Breast cancer surgery ranks second to amputation of extremities for chronic neuropathic pain. Prevalence of PPBCS is as high as 65% in women between ages of 30 and 49; 40% in women between ages of 50 and 59 and 25% among women 60 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…The established clinical grading system for PPBC reflects its heterogeneity and portends to a complex of interacting risk factors. [6,7] PPBCS can present with symptoms of sharp pain, burning pain, paresthesia, hyperesthesia and numbness, which can be exacerbated with quality and intensity of the noxious stimuli. [8] So far, a spectrum of clinical factors ranging from the method of surgical intervention, radiation therapy, the age of the affected person, body mass index, lymphedema and psychological factors, i.e.…”
Section: Introductionmentioning
confidence: 99%